The cat in the hat (I Can Read It All By Myself Beginner Books, ,, 1985)
Two children sitting at home on a rainy day are visited by the cat who shows them some tricks and games.

Dr. Seuss's sleep book (Random House, 1962)
Tells, in verse, what happens when all ninety-nine zillion nine trillion and three creatures in the world go to sleep.

Fox in socks (Beginner Books, 1993)
A collection of tongue twisters that is "an amusing exercise for beginning readers.